Immunological evaluation of the intestinal mucosa of broiler chicks treated with Lactobacillus Spp. and challenged with Salmonella Enteritidis - Okamoto, AS [UNESP] (2007)
This study aimed at the antibody production by intestinal mucosa of broilers chicks were orally inoculated with Lactobacillus spp. at one and/or 21 days of age, and subsequently challenged with Salmonella enterica, subspecies enterica, serotype Enteritidis (S. Enteritidis). A total number of 288 drug-free broiler chicks was divided into 6 groups (groups A, B, C, D, E, and F), according to age at Lactobacillus spp. inoculation and SE challenge. The intestinal mucosa immune response was determined as the production of immunoglobulin A against S. Enteritidis, and evaluated by the Enzyme-Linked Immunosorbent Assay (ELISA) technique in intestinal washing fluid. Groups treated with Lactobacillus spp. presented higher IgA production only when the chicks were challenged with S. Enteritidis at 21 days of age. Nevertheless, the expected stimulus for intestinal mucosa antibody production induced by Lactobacillus spp was observed in only some of the treated groups, demonstrating that the protocol utilized in the present experiment resulted in few beneficial effects for chicks, particularly during the first days of life.